Different Forms of Hypothyroidism in Infants with Maternal Graves' Disease: A Case Series - Lordudass, Alexis Anand Dass; Wong, Jeanne Sze-Lyn; Selveindran, Nalini; Hong, Janet Yeow Hua (Journal of the ASEAN Federation of Endocrine Societies, 2024)
Infants of mothers with Graves’ disease (GD) may develop central hypothyroidism (CH) due to exposure of the foetal hypothalamic-pituitary-thyroid axis to higher-than-normal thyroid hormone concentrations, primary hypothyroidism (PH) due to transplacental passage of maternal thyroid stimulating hormone receptor antibody (TRAb), antithyroid drugs (ATD) or thyroid dysgenesis secondary to maternal uncontrolled hyperthyroidism. We describe two infants with PH and four infants with CH born to mothers with poorly controlled Graves' disease. All infants required levothyroxine and had normal developmental milestones. While national guideline consensus for high thyroid stimulating hormone (TSH) on neonatal screening is well-established, thyroid function tests (TFTs) should be serially monitored in infants with low TSH on screening, as not all mothers with Graves’ disease are diagnosed antenatally.